Improving Students Reading "Text Recount" by Skimming Technique For High School Students - Hutabarat, Frans Putra; Gultom, Yuly Winarti; Panjaitan, Ribka; Ginting, Selliani; Sinabutar, Angelina; Silalahi, Dumaris E (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the improvement of students' reading comprehension in recount texts through Picture Stories in SMA NOMMENSEN to determine the factors that influence the improvement of students' reading comprehension of recount texts in SMA NOMMENSEN. This study analyzes the average score of each test to determine the improvement of students' reading comprehension in recount texts after the activity (action) is carried out. The results of the study indicate that the implementation of picture stories can improve students' reading comprehension. There is an improvement in the average score of students from the text. This can be seen from the results of the average score of students in test cycle 1 70. Increased to 80.61 in test cycle II. It can be concluded that researchers choose picture stories to understand texts as one of the media to improve teaching and learning to read recount texts.